Dealing with the female in some Kurdish folklore stories in the Bahdinan region: it is a feminist study according to the principles of the liberal school of feminism - Pirmoos, Huda; Abdullrahman, Hussein (Humanities Journal of University of Zakho, 2022)
If we look at the society and the events in the society, we will see that woman was one of the main figures in the old and modern life of Kurdistan, especially if we go back to the old life of the Kurds without them, life would have been very difficult. This was clearly reflected in the songs, stories, and all literary branches of Kurdish folklore. This movement gradually entered literature and as literary criticism, it began to evaluate works. The criticism of feminism as a new critical movement in the recent century is highly valued. The feminist notion values females in all aspects. This research conducts questions and problems of the female gender in Kurdish folklore stories particularly, in Bahdinan areas. Finding out how far a Kurdish folklore story of Bahdinan areas fairly looks at both genders? In a society that male gender is dominant. How far the narrator of folklore stories has avoided the male dominant notion while narrating? Has the male domination notion had effects on Kurdish folklore stories of Bahdinan areas? This research consists of an introduction and two chapters. The first chapter is the theoretical part that contains two parts: the first part consists of definitions of folklore stories, the characteristics of the folklore stories, how to narrate, the importance of folklore stories, and their types. The second part deals with feminism such as aspects, definitions, feminism movements, its history, and the schools of feminist criticism in general and the (Liberal Feminism) in particular. In the second chapter, several Kurdish folklore stories of Bahdinan areas have been used practically in this research. This research has found out some results, male dominance in Kurdish folklore stories of Bahdinan areas is dominant. In the past and present as well as in the Kurdish society of Bahdinan areas particularly the males are dominant. The notion of male dominance has been moved and inherited from one generation to another.